1978
DOI: 10.1161/01.res.43.4.632
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lathyrogen beta-amino proprionitrile (BAPN) on the mechanical properties of experimentally hypertrophied rat cardiac muscle.

Abstract: SUMMARY yS-Amino proprionitrile (BAPN) at dietary concentrations of 1, 5, and 10 g BAPN/kg rat chow was administered to rats for 14-21 days following surgical constriction of the ascending aorta. Five and 10 g BAPN/kg rat chow prevented the increase in left ventricular collagen content which occurred with cardiac hypertrophy in rats following aortic constriction. In spite of this block in the increase in collagen in the ventricles, isolated trabecular muscles from hypertrophied hearts showed a decrease in maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
32
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 33 publications
5
32
1
Order By: Relevance
“…Furthermore, the constant hydroxyproline concentration as hypertrophy developed also is opposite that observed by others in pressure-induced cardiac hypertrophy (3,5,6). Comparison of this and previous studies revealed that these differences could not be attributed to differences in species studied (2,4,5) or extent of hypertrophy (1,2,4).…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…Furthermore, the constant hydroxyproline concentration as hypertrophy developed also is opposite that observed by others in pressure-induced cardiac hypertrophy (3,5,6). Comparison of this and previous studies revealed that these differences could not be attributed to differences in species studied (2,4,5) or extent of hypertrophy (1,2,4).…”
Section: Discussioncontrasting
confidence: 68%
“…The anatomic determinants of passive stiffness have not been elucidated completely although there is considerable evidence that the connective tissue matrix and its collagen component play a major role (3,28). Many authors have measured collagen as hydroxyproline since traditionally it has been believed that hydroxyproline formed a constant fraction of mammalian collagen (29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to impaired CO and loss of heart contractility (Pfeffer et al 1979, Fellenius et al 1985, Pfeffer & Pfeffer 1987, the arterial mean BP could not be reached. In case of an increase of left ventricular filling pressure (Pfeffer et al 1979, Pfeffer & Pfeffer 1987, an increase of myocardial stiffness and wall tension due to fibrosis (Bing et al 1978, Hess et al 1981, Thiedemann et al 1983, Carroll et al 1989, Jalil et al 1989, there is no increase in LVPs because of the loss of heart contractility and therefore loss of pressure in the systole of the infarcted rat heart (Bing et al 1995).…”
mentioning
confidence: 99%